EVALUATION OF INDONESIA’S READINESS FOR EARTH OVERSHOOT DAY 2045 THROUGH ECOLOGICAL FOOTPRINT, BIOCAPACITY, AND RESOURCE CONSUMPTION PROJECTION ANALYSIS - Darmatama, Iman; Pratama, Zakhi Restu; Maulana, Fahrul Rozi (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Rapid population growth, increasing resource consumption, and the implementation of the Indonesia Gold 2045 vision are expected to intensify pressure on natural resources, making the assessment of Indonesia's ecological readiness increasingly important. This study evaluates Indonesia’s readiness to face Earth Overshoot Day 2045 by integrating Ecological Footprint (EF), biocapacity (BC), ecological deficit, and Earth Overshoot Day (EOD) projections within the Indonesia Gold 2045 framework. A quantitative descriptive approach was employed using historical data from the National Footprint and Biocapacity Accounts (NFBA) for the period 2005-2024. Trend analysis and historical linear trend extrapolation were applied to project future ecological conditions under a Business-as-Usual (BAU) scenario, assuming that current patterns of resource consumption and environmental management continue without significant policy intervention. The results indicate that Indonesia’s Ecological Footprint increased from 1.12 to 1.56 gha per capita, while biocapacity declined from 1.48 to 1.20 gha per capita, shifting the country from an ecological reserve to an ecological deficit since approximately 2015. Under the BAU scenario, the Ecological Footprint is projected to reach 2.18 gha per capita, whereas biocapacity is projected to decline to 0.90 gha per capita by 2045, resulting in an earlier occurrence of Earth Overshoot Day and a widening ecological deficit. These findings demonstrate the value of integrating Ecological Footprint, biocapacity, ecological deficit, and Earth Overshoot Day into a single analytical framework for assessing long-term ecological sustainability. The projected trends further indicate that strengthening resource efficiency, accelerating the transition to renewable energy, restoring ecosystems, and promoting circular economy practices will be essential to reduce ecological pressure and support Indonesia's sustainable development toward 2045.